Exchange Rates and Economic Fundamentals : A Methodological Comparison of BEERs and FEERs - MacDonald, Ronald (IMF Working Papers; Working Paper ;, 1998)
This paper compares two approaches for examining the extent to which a country's actual real effective exchange rate is consistent with economic fundamentals: the FEER approach, which involves calculating the real exchange rate that equates the current account at full employment with sustainable net capital flows, and the BEER approach, which uses econometric methods to establish a behavioral link between the real rate and relevant economic variables. An exchange rate model is estimated for the G-3 currencies to provide illustrative comparisons of BEERs and FEERs.